ANALISA EFISIENSI KALOR PADA ALAT PENETAS TELUR - Fuazen Fuazen; Elandi Elandi; Gunarto Gunarto (Suara Teknik : Jurnal Ilmiah, 2019)
Machine hatches to constitute one of media which as box with in such a way construction face so heat in it doesn't be discarded in vain. Temperature in box can be managed appropriate needed hot degree up to hatch period. In ranch area in particular in duck ranch, faced problem is how for incubate  duck egg in number a lot of and in the period of that coincides. Since duck parent ability in incubate its circumscribed egg, which is ± 15 eggs every parented ducks. This becomes because problem flesh requirement and duck egg at market that muchly. Machine dimension incubate capacity 100 with longing machine incubate are 600 mm, with Broad 450 mm, and Tall 450 mm and can keep temperature 38  o C until 41 o C  so gets to be utilized on duck egg brood. kalor's charges on spatial incubator machine is as big as 47,48 kcal / h and energy that is given on incubator machine as big as 72,6 Watts. So gotten by happening kalor efficiency on incubator machine room of charges compare count kalor that needful incubator machine with kalor's charges that is given on incubator machine is as big as 76%.